Research design explained - Mitchell, Mark L.; Jolley, Janina M. (Wadsworth Cengage Learning, 2013)
RESEARCH DESIGN EXPLAINED, Eighth Edition helps readers appreciate the excitement of science research and its relevance to psychology by explaining concepts clearly and using real-life analogies and examples. Focusing on important, fundamental concepts and demonstrating the logic behind research design, authors Mitchell and Jolley help readers go beyond simply memorizing terms to develop a true understanding of research design